Sustainability Leadership : a Swedish approach to transforming your company, your industry and the world - Henriksson, Henrik; Grunewald, Elaine Weidman (Ascent Audio, 2021)
As CEOs and business leaders navigate a world of complex global challenges, sustainability is no longer optional but a business imperative. In this book, two sustainability leaders with decades of experience-Henrik Henriksson, CEO of Scania and Elaine Weidman Grunewald, cofounder of the AI Sustainability Center, and former chief sustainability and public affairs officer at Ericsson-offer a simple but powerful three-step model for leading an organization on a sustainability transformation journey that aims at big, audacious, world-changing goals. Honest about the dilemmas but bullish on the opportunities, the authors advise leaders on how to accelerate sustainability in their organizations told through a Swedish lens, where the country's values and culture permeate the boardroom and the C-suite, bringing a unique clarity and conviction to leading with integrity. In practical insights gleaned from the authors' own experience, the book takes leaders through the three phases of sustainability leadership: from establishing a solid foundation rooted in purpose, culture, values, principles and consistent, credible leadership, to integrating sustainability into the core business, and then to executing a vision that not only shifts the direction of the company but can change an entire industry, and even the world.